Interrelations between Modern Applied Arts and Visual Arts - Veljataga, Pilė (Problemos, 1986)
The author discusses .the deployment of the means of the artistic language of visual arts in the works of applied arts. The phenomenon is characterized by the growth of meaning in the represented motive. It is argued that the value of such artistic works depends upon proper synthesis of the means of both types of art. The synthesis is considered to be appropriate if it enriches applied arts with the weight of meaning without harming its decorative expressiveness.